A literature review of cost-effectiveness of intravenous recombinant tissue plasminogen activator for treating acute ischaemic stroke - Joo, Heesoo (Stroke Vasc Neurol, 2017)
BACKGROUND: Intravenous recombinant tissue plasminogen activator (IV rtPA) is recommended treatment for patients with acute ischaemic stroke, but the cost-effectiveness of IV rtPA within different time windows after the onset of acute ischaemic stroke is not well reviewed. AIMS: To conduct a literature review of the cost-effectiveness studies about IV rtPA by treatment times. SUMMARY OF REVIEW: A literature search was conducted using MEDLINE, EMBASE, CINAHL and Cochrane Library, with the keywords acute ischemic stroke, tissue plasminogen activator, cost, economic benefit, saving and incremental cost-effectiveness analysis. The review is limited to original research articles published during 1995–2016 in English-language peer-reviewed journals. We found 16 studies meeting our criteria for this review. Nine of them were cost-effectiveness studies of IV rtPA treatment within 0–3 hours after stroke onset, 2 studies within 3–4.5 hours, 3 studies within 0–4.5 hours and 2 studies within 0–6 hours. IV rtPA is a cost-saving or a cost-effectiveness strategy from most of the study results. Only one study showed incremental cost-effectiveness ratio of IV rtPA within 1 year was marginally above US$50 000 per quality-adjusted life year threshold. IV rtPA within 0–3 hours after stroke led to cost savings for lifetime or 30 years and IV rtPA within 3–4.5 hours after stroke increased costs but still was cost-effective. CONCLUSIONS: The literature generally showed that IV rtPA was a dominant or a cost-effective strategy compared with traditional treatment for patients with acute ischaemic stroke without IV rtPA. The findings from the literature lacked generalisability because of limited data and various assumptions.